Population and genome-wide association studies of Sclerotinia sclerotiorum isolates collected from diverse host plants throughout the United States - Poudel, Roshan Sharma; Belay, Kassaye; Nelson, Berlin; Brueggeman, Robert; Underwood, William (Frontiers in Microbiology, 2023)
Sclerotinia sclerotiorum is a necrotrophic fungal pathogen causing disease and economic loss on numerous crop plants. This fungus has a broad host range and can infect over 400 plant species, including important oilseed crops such as soybean, canola, and sunflower. S. sclerotiorum isolates vary in aggressiveness of lesion formation on plant tissues. However, the genetic basis for this variation remains to be determined. The aims of this study were to evaluate a diverse collection of S. sclerotiorum isolates collected from numerous hosts and U.S. states for aggressiveness of stem lesion formation on sunflower, to evaluate the population characteristics, and to identify loci associated with isolate aggressiveness using genome-wide association mapping. We observed a broad range of S. sclerotiorum genetic and pathogenic diversity 2 aggressiveness among 219 isolates evaluated for stem lesion formation on two sunflower inbred lines, and only a moderate correlation between aggressiveness on the two lines. We performed genotyping by sequencing to identify single nucleotide polymorphisms among isolates and used these markers to assess population differentiation across hosts, regions, and climatic conditions. These evaluations revealed genetic differentiation between populations from warmer climate regions compared to cooler regions. Finally, we carried out a genome-wide association study of isolate aggressiveness and identified three loci significantly associated with aggressiveness on sunflower.Functional characterization of candidate genes at these loci will likely improve our understanding of the virulence strategies used by this pathogen to cause disease on a wide array of agriculturally important host plants.